Antimicrobial resistance: A round table discussion on the "One Health" concept from the Gulf Cooperation Council Countries. Part Two: A focus on Human Health. Issue 6 (November 2018) - Balkhy, Hanan H.; Zowawi, Hosam M.; Alshamrani, Majid M.; Allegranzi, Benedetta; Srinivasan, Arjun; Al-Abdely, Hail M.; Somily, Ali M.; Al-Quwaizani, Mohammad A.; ,; Al-Maani, Amal Saif; Al-Abdely, Hail M.; Balkhy, Hanan; et al.
Abstract: The Gulf Cooperation Council Center for Infection Control (GCC-IC) has moved forward over the past several years on the antimicrobial resistance (AMR) agenda. Many of the GCC countries have now developed a national plan to combat AMR and have engaged the leadership of the involved sectors in the discussion on how to mitigate this threat. During the first meeting for the GCC-IC center on AMR, which took place early 2015, the roadmap for combating AMR was developed[1] and since then much more has been done. We present here the discussion that took place during the second GCC-IC center meeting on AMR where not only have the countries presented their progress, but we conducted 2 round table discussions inviting international and regional experts in the field to share their thoughts, progress and knowledge on this topic[2] . Within is the 2nd round table discussion at the 2017 GCC AMR meeting which took place in Riyadh, Saudi Arabia, April 2017. Where the 1st round table discussion during this meeting addressed the role of leadership in managing AMR[2] .